Decreased Thickness of Primary Motor Cortex in Primary Lateral Sclerosis - Butman, J.A.; Floeter, M.K. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Primary lateral sclerosis (PLS) is a rare form of motor neuron disease characterized by upper motor neuron dysfunction. Because pathologic examination has revealed a loss of neurons in the motor cortex of patients with PLS, we sought to confirm and extend this finding by using MR imaging to measure cortical thickness.METHODS: Seven patients with PLS and 7 age-matched neurologically normal control subjects were examined with heavily T1-weighted short-τ inversion recovery (STIR) MR imaging performed at 3T. Cortical thickness in the anterior and posterior banks of both the central and precentral sulci were measured.RESULTS: Primary motor cortex (M1) was significantly thinner in patients with PLS than M1 in healthy control subjects, measuring 2.32 ± 0.21 mm compared with 2.79 ± 0.18 mm (P = .0008). Cortical thickness did not differ between the 2 groups for primary sensory cortex or for the anterior or posterior banks of the precentral sulcus. Therefore, loss of gray matter was specific to motor cortex. Although this difference was modest, cortical thickness discriminated between the 2 groups; only 1 PLS case was within the range of normal measurements.CONCLUSION: Decreased thickness of M1 on the anterior bank of the precentral sulcus in patients with PLS, demonstrable by MR imaging, indicates a selective loss of upper motor neurons in this disease. Measurements of cortical thickness by MR imaging may provide a useful biomarker for diagnosis and study of upper motor neuron diseases.